Wadon Wadas: Women’s Resistance in Agrarian Conflict of Andesite Mining Construction Policy in Purworejo Regency - Humaidi, M Wildan (UIN Sunan Kudus, 2023)
Women play a critical role in agrarian social relations. Women’s interests must always be considered in land governance and utilization policies. The construction of andesite mining in Wadas Village as one of the land development policies is considered to have taken away women’s interests and harmed women’s living space. This study employed a qualitative research method. With an ecofeminism approach and an analytical description technique, This research aimed to elaborate on the role of women in the agrarian struggle against andesite mining and the construction of the Bener Dam in Wadas Village. Based on the analysis, it can be concluded that Wadon Wadas, as one of the primary actors in agrarian social relations, has played a critical role in determining the continuity and preservation of agrarian resources in Wadas Village. Wadon Wadas’ involvement in a variety of protests can be explained, such as participating in litigation efforts to overturn the Governor’s policy in court, mujahadah (spiritual struggle), weaving besek (container made of woven bamboo), and sharing food as a cultural and symbolic action, as well as their resistance during the repressive physical conflict by the police.